History and Empirical: The Influence of Badan Usaha Milik Desa (BUMDes) as Joint Venture on the Brotherhood Principle on Village Economic Independence - Burhanuddin Burhanuddin*; Agussalim Agussalim; Wahyuni Wahyuni (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to analyze and describe "Historical and Empirical: The Influence Badan Usaha Milik Desa (BUMDes) as a Joint Venture on the Principle of Brotherhood on Village Economic Independence". Respondents to this study were BUMDes administrators and the people of Nggembe Village, Bolo District, Bima Regency, totaling 47 people. The research instruments are questionnaires and documentation. Data were analyzed using simple linear regression analysis. The results of the research in terms of the history of the establishment of BUMDE are venture entities whose main motive is not solely seeking economic profit, but rather community-based empowerment activities by utilizing village potential so that they have added economic value based on the spirit of joint on the principle of brotherhood. Empirically, BUMDes as a joint venture on the principle of kinship has a significant and positive effect on village economic independence. The managerial implications of this research are that the implementation of a joint business on the principle of kinship through the business partnership movement developed by BUMDEs is a major factor in success in business management.